The Role of Foodscape in Enhancing the Attraction of Gastronomic Tourism in Neglasari Village, Tasikmalaya Regency - Lafifah, Pipin; Turgarini, Dewi; Putri, Dias Pratami (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
The diversity of agricultural products, locally processed goods, and culinary traditions passed down through generations make Neglasari Village have a unique foodscape. This potential can be utilized to develop gastronomic tourism, attract tourists, and enhance the local economy. Studies mapping foodscapes in Indonesian villages, especially those linking local potential with gastronomic tourism appeal, are still limited. This research aims to identify tourist attractions in Neglasari Village, Tasikmalaya Regency, and analyze the potential of the foodscape as a support for gastronomic tourism through the role of the nona helix. The research method employs a qualitative descriptive approach through observation, interviews, and documentary studies. The results show that Neglasari Village has strong potential for natural, cultural, and culinary tourist attractions. The village's foodscape includes a diversity of local dishes based on agricultural raw materials and traditional processed foods with high cultural and economic value. The collaboration of nona helix proved effective in strengthening promotion, enhancing the capacity of business actors, and developing the culinary supply chain.